Comparison of Two Instructional Strategies for Students with Autism to Read Sight Words - AKÇİN, FATMA NUR (My University, 2013)
Problem Statement: Literacy skills are extremely important for all individuals, especially children with autism, because these skills provide a channel for educational assessment and learning as well as enhance vocational opportunities, promote self-expression, and facilitate independent living. Some individuals with autism cannot acquire academic literacy skills, though they can acquire the functional literacy skills that are essential for them to live, work and participate in social life. W ord reading is the first step of functional literacy instruction. Previous studies in literature have compared the effectiveness of constant timedelay and stimulus fading procedures within sight word reading instruction. These studies included participants with mild and moderate mental retardation. However, it is surprising that there are so few similar studies conducted among individuals with autism. in addition, existing studies have revealed that teachers lack the specific information and skills necessary to teach literacy skills to individuals with autism. This study will contribute to literature comparing the effectiveness and efficiency of constant time-delay and stimulus fading strategies in teaching students with autism to read sight words. Purpose of Study: The purpose of this study was to compare the effectiveness and efficiency of constant time-delay and stimulus fading strategies in assisting three students with autism to read sight words. Met/ıods: Participants were three students with autism, ranging in age from 12 to 14. A five-word set was determined for each teaching strategy, and both sets were taught to the participants. The teachers and mothers of the participants were interviewed before selecting the target words. An adapted alternating-treatments design was used to compare the effectiveness and efficiency of constant time-delay and stimulus fading strategies for students with autism to read sight words. Inter-observer and procedural reliability data were collected. Findings and Results: Target words were acquired by students during the intervention sessions. All three participants were able to generalize reading these target words through the materials of different writing styles, font sizes and letter styles (upper- and lower-cases). Permanent effects of the instructional procedures were observed in maintenance sessi ons. Conclusions and Recommendations: The results indicated that both strategies were effective; however, the constant time-delay strategy was more efficient in terms of the number of trials required to achieve performance criterion. Keywords: Autism, sight word reading, constant time-delay, stimulus fading, single-subject design
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Özel Eğitim; Zihin Engelliler Öğretmenliği; Social Sciences and Humanities; Education; Special Education; Teacher Training Mentally-Retarded Children; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, ÖZEL; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SPECIAL; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Autism; sight word reading; constant time-delay; stimulus fading; single-subject design